Writing the annotated bibliography : a guide for students & researchers - Beatty, Luke; Cochran, Cynthia A. (New York, NY : Routledge, 2020)
"This comprehensive and practical guide covers the elements, style, and use of annotated bibliographies in the research and writing process for any discipline; key disciplinary conventions; and tips for working with digital sources. Written jointly by a library director and a writing center director, this book is packed with examples of individual bibliography entries and full bibliography formats for a wide range of academic needs. Online resources include sample bibliographies, relevant web links, printable versions of checklists and figures, and further resources for instructors and researchers. Writing the Annotated Bibliography is an essential resource for first-year and advanced composition classes, courses in writing across the disciplines, library science instruction programs, and academic libraries at the secondary level and beyond. It is suitable for both undergraduate and graduate students and for researchers at all levels"--
Setting the stage -- Citation & documentation styles -- The format & look of the annotated bibliography -- Types of annotations -- Annotating different kinds of sources -- Getting sources into your annotated bibliography -- Crunch time: Annotated bibliography in process -- Tools & strategies for working online -- Sample annotated bibliographies.
OCLC-licensed vendor bibliographic record.
Keywords: Bibliography -- Methodology; LANGUAGE ARTS & DISCIPLINES / Composition & Creative Writing; EDUCATION / Study Skills